An Analysis Of Lesson Plan Designed By Senior High School English Teacher - Mulyawati, Ririn Eva (2012)
The research is conducted to describe the quality of lesson plan designed by the teacher in senior high school in Surakarta, especially in formulating indicators, designing the teaching learning activity , and desining evaluation based on the PERMEN 41 (Regulation of National Education Minister number 41). The writer limits the research only on the suitability of indicator, teaching learning process, and evaluation of lesson plans designed by English teachers of senior high school in Surakarta on the term II in academic year 2011/2012. The writer employs descriptive evaluative research as the type of the study. The writer collects the data, classifies them, and finally draws conclusion based on the data analysis. The method of collecting data is documentation and field note. The data are lesson plans taken from SMA N 2, SMA N 5, SMA N 6, SMA N 7 and SMA N 8 Surakarta. The data are divided into three, namely design of indicators, design of teaching learning process, and design of evaluation. The tehnique for analyzing data is descriptive. The writer analyzes the sutaibily of design of indicator, teaching learning process, and evaluation based on PERMEN 41 (Regulation of National Education Minister number 41). The writer draws conclusion of the analysing the data by making the percentage of each datum. Based on the analysis,the percentage of indicator in narrative, hortatory exposition, and spoof are 20,8%. The percentage is categorized as poor based on the theory onSuharsimi (1993:201). The total percentage of the design of teaching learning process in narrative, hortatory exposition, and spoof is 58,8%. Based on the theory onSuharsimi (1993:201), the percentage shows that the qualities of the designs of teaching learning process are good. The total percentage of the design of evaluation in narrative, hortatory exposition, and spoof is 25,3%. Based on the theory on Suharsimi (1993:201), the precentage shows that the designs of evaluation are poor.